2014
DOI: 10.1109/jmems.2013.2290994
|View full text |Cite
|
Sign up to set email alerts
|

A Large Piston Displacement MEMS Mirror With Electrothermal Ladder Actuator Arrays for Ultra-Low Tilt Applications

Abstract: A large displacement piston motion micromirror is designed, fabricated, and tested with device features tuned to applications requiring ultralow tilt. The fabricated MEMS mirror is based on electrothermal actuation and has a footprint of 1.9mm × 1.9mm with a mirror aperture of 1 mm. The application optimized device holds key features of ultralow maximum tilt of 0.25°and a strongly linear motion of 90 µm achievable at only 1.2 V. This device is further characterized in an interferometric system to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…The change in the bimorph temperature also alters the resistance R(T h ) of the Pt heater. Currently, analytical models can be obtained only for simple geometries, so numerical models such as finite element method are usually used for most practical problems [14], [16]. However, in order to design a closedloop control system analytically and attain ultra-low tilting, it is essential to develop a complete electrothermomechanical model in the form of transfer function.…”
Section: A Device Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in the bimorph temperature also alters the resistance R(T h ) of the Pt heater. Currently, analytical models can be obtained only for simple geometries, so numerical models such as finite element method are usually used for most practical problems [14], [16]. However, in order to design a closedloop control system analytically and attain ultra-low tilting, it is essential to develop a complete electrothermomechanical model in the form of transfer function.…”
Section: A Device Descriptionmentioning
confidence: 99%
“…Later, Wu et al employed a corner-cube retroreflector and a dual-reflective MEMS mirror and obtained an effective scan range of 308 μm [15], but this design only ensures the overlap of the two light beams respectively reflected back from the MEMS mirror and the fixed mirror while the wavefront distortion caused by the mirror tilt still exists. Samuelson et al proposed a laddered inverted-series-connected (ISC) electrothermal actuator design and demonstrated a low uncompensated tilt of 0.25°over its full 90 μm displacement range [16] and the mirror tilt was reduced to 0.004°using a pair of ratio optimized drive signals, but the achievable OPD was only 95 μm in a FTS setup [17]. To further reduce the uncompensated tilt, Xie et al reported an MEMS mirror with a three-level ladder ISC actuator design and an unique configuration of 16 ISC actuators and demonstrated a very small uncompensated tilting of less than 0.03°over the full actuation range [13] but this tilt angle is still one order of magnitude larger than the optimal tilt.…”
mentioning
confidence: 99%
“…Recently, some new applications include response surface method [7] and ghost imaging [8]. On the basis of actuation method, torsional micromirrors can be classified into different types: electrothermal [9], electrostatic [10], electromagnetic [11,12], piezoelectric [13], and so forth. Recently, the electromagnetic micromirrors have attracted special attention owing to their ability to produce large scan angles with low voltage and remote actuation (meaning that the mirrors can be controlled by the non-contact force at a distance).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the speed of actuation will depend on the thermal dynamics of the system, making it the slowest mechanism of all for devices of similar size and thermal mass. The power consumed in this mechanism can be lower than the EM, but higher than the ES and PE, since the temperature increase depends on the amplitude of the applied current, which can be as high as 252 mA for maximum displacement [9]. …”
Section: Introductionmentioning
confidence: 99%